Efficacy and Safety of Dexmedetomidine for Prolonged Sedation in the PICU: A Prospective Multicenter Study (PROSDEX)*. Issue 7 (July 2020) - Sperotto, Francesca; Mondardini, Maria C.; Dell'Oste, Clara; Vitale, Francesca; Ferrario, Stefania; Lapi, Maria; Ferrero, Federica; Dusio, Maria P.; Rossetti, Emanuele; Daverio, Marco; Amigoni, Angela
Abstract : Objectives: We sought to evaluate dexmedetomidine efficacy in assuring comfort and sparing conventional drugs when used for prolonged sedation (≥24 hr) in critically ill patients, by using validated clinical scores while systematically collecting drug dosages. We also evaluated the safety profile of dexmedetomidine and the risk factors associated with adverse events. Design: Observational prospective study. Setting: Nine tertiary-care PICUs. Patients: Patients less than 18 years who received dexmedetomidine for greater than or equal to 24 hours between January 2016 and December 2017. Interventions: None. Measurements and Main Results: One-hundred sixty-three patients (median age, 13 mo; interquartile range, 4–71 mo) were enrolled. The main indication for dexmedetomidine use was as an adjuvant for drug-sparing (42%). Twenty-three patients (14%) received dexmedetomidine as monotherapy. Seven percent of patients received a loading dose. The median infusion duration was 108 hours (interquartile range, 60–168 hr), with dosages between 0.4 (interquartile range, 0.3–0.5) and 0.8 µg/kg/hr (interquartile range, 0.6–1.2 µg/kg/hr). At 24 hours of dexmedetomidine infusion, values of COMFORT-B Scale ( n = 114), Withdrawal Assessment Tool-1 ( n = 43) and Cornell Assessment of Pediatric Delirum ( n = 6) were significantly decreased compared with values registered immediately pre dexmedetomidine ( p < 0.001, p < 0.001, p = 0.027). Dosages/kg/hr of benzodiazepines, opioids, propofol, and ketamine were also significantly decreased ( p < 0.001, p < 0.001, p = 0.001, p = 0.027). The infusion was weaned off in 85% of patients, over a median time of 36 hours (interquartile range, 12–48 hr), and abruptly discontinued in 15% of them. Thirty-seven percent of patients showed hemodynamic changes, and 9% displayed hemodynamic adverse events that required intervention (dose reduction in 79% of cases). A multivariate logistic regression model showed that a loading dose (odds ratio, 4.8; CI, 1.2–18.7) and dosages greater than 1.2 µg/kg/hr (odds ratio, 5.4; CI, 1.9–15.2) increased the odds of hemodynamic changes. Conclusions: Dexmedetomidine used for prolonged sedation assures comfort, spares use of other sedation drugs, and helps to attenuate withdrawal syndrome and delirium symptoms. Adverse events are mainly hemodynamic and are reversible following dose reduction. A loading dose and higher infusion dosages are independent risk factors for hemodynamic adverse events. Abstract : Supplemental Digital Content is available in the text.